2003
DOI: 10.1002/esp.1037
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and simulation of wind erosion, roughness degradation and residue decomposition on an agricultural field

Abstract: The Wind Erosion Prediction System (WEPS) includes submodels to simulate soil erosion by wind, roughness degradation and residue decomposition. These WEPS submodels were tested using data measured on a 600 m by 415 m farmer's field, planted with winter wheat, near Burlington, Colorado, USA. Big Spring Number Eight (BSNE) samplers were used to measure wind blown sediment flux and automated devices (Sensits) detected saltating sediment. A weather station recorded relevant meteorological data. Detailed measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Soil crust and crop cover have a large influence on the erodibility of the soil and the transport capacity (Hagen, 1996;Molion and Moore, 1983;Rice et al, 1997;Visser et al, 2005). Van Donk and Skidmore (2003) concluded that the WEPS erosion submodel overestimates the protective role of small wheat plants in simulating erosion.…”
Section: Resultsmentioning
confidence: 99%
“…Soil crust and crop cover have a large influence on the erodibility of the soil and the transport capacity (Hagen, 1996;Molion and Moore, 1983;Rice et al, 1997;Visser et al, 2005). Van Donk and Skidmore (2003) concluded that the WEPS erosion submodel overestimates the protective role of small wheat plants in simulating erosion.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing CUMR produced higher degradation rates of Kr and Crr created by all tillage tools, in both soils. Some authors proposed the use of only the rain amount or rain energy as a single parameter (Van Donk and Skidmore, 2003;Zobeck and Onstad, 1987) to evaluate both soil roughness decay using exponential negative relations (Onstad et al, 1984;Potter et al, 1990;Römkens and Wang, 1985;.…”
Section: Resultsmentioning
confidence: 99%
“…A wind tunnel study indicated that the threshold friction velocity of a dry and smooth silt loam was 0·34 m s −1 (Goossens, 2001). Van Donk et al (2003) examined the performance of WEPS on a silt loam sown to winter wheat in Colorado. The WEPS erosion submodel predicted no erosion despite a measured soil loss of 600 kg ha −1 during a singular event.…”
Section: Resultsmentioning
confidence: 99%